2008
DOI: 10.1002/acp.1470
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to postidentification feedback is affected by source credibility

Abstract: How much a person is affected by postidentification feedback is dependent on the credibility of the person giving the feedback. Seven hundred and ninety participants across three experiments viewed a crime video, made judgments from a line-up, were provided with co-witness and/or outcome feedback (from police officers [high credibility] or children [low credibility]), and answered testimony-relevant questions (e.g. How good a view did you get of the person in the video?). The aim was to find out how high versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 36 publications
5
54
0
2
Order By: Relevance
“…Although the choice of what makes someone a "memory" expert in the context of memory recall is not so clear-cut, we reasoned that policemen would be viewed as more likely to be vigilant and practiced in tasks involving the memory of crimes. Moreover, the previously outlined study by Skagerberg and Wright (2009) showed an effect for a manipulation using police officers as experts.…”
Section: This Studymentioning
confidence: 91%
“…Although the choice of what makes someone a "memory" expert in the context of memory recall is not so clear-cut, we reasoned that policemen would be viewed as more likely to be vigilant and practiced in tasks involving the memory of crimes. Moreover, the previously outlined study by Skagerberg and Wright (2009) showed an effect for a manipulation using police officers as experts.…”
Section: This Studymentioning
confidence: 91%
“…Witnesses have a distinct trust in police interviewers (Semin & Poot, 1997), particularly those with greater perceived credibility or knowledge (Skagerberg & Wright, 2009;Smith & Ellsworth, 1987). It also appears that memory over time is more impressionable when the original message is delivered by a source with authority (Underwood & Pezdek, 1998).…”
mentioning
confidence: 92%
“…Studies also show that people are more influenced by confident people and by people who they think should have good memories. For example, Skagerberg and Wright (2009) told participants that their memories were either the same as or different from memories of either children or police officers. They found that providing information about children's memories did not affect the participants' beliefs, but telling them about police officers' memories did.…”
Section: Social Recognition Test Proceduresmentioning
confidence: 99%